Keberkesanan kelab Malaysiaku dalam memperkukuhkan semangat jati diri dikalangan pelajar sekolah - Norazila, Mat Zin (2024)
As a developing nation, Malaysia emphasizes the creation of 'good citizens' imbued with high values of patriotism, notably through the National Service Training Program (PLKN) and the National Civics Bureau (BTN). However, following the 14th General Election (GE-14), the government decided to shut down PLKN and BTN, shifting the responsibility of fostering patriotism among the youth to other organizations. One such organization is Kelab Malaysiaku, established by the Department of Information in collaboration with the Ministry of Education to instill a sense of patriotism among school students. This study aims to identify the direction of school students in planning their future, evaluate the sense of patriotism among them in ensuring national development, and examine the role of Kelab Malaysiaku in shaping students with a strong national identity, specifically in the state of Perlis. The research employs a qualitative approach through face-to-face interviews with seven selected school student respondents and participant observation by the researcher, who serves as an information officer in Perlis. The findings indicate that all respondents agree their involvement in Kelab Malaysiaku provides various benefits and allows them to learn a wide range of nation-related knowledge, enhancing their love for the country. They also unanimously agree that their participation in every activity organized by Kelab Malaysiaku positively impacts their national values. Therefore, it is recommended that Kelab Malaysiaku continues its activities, and more non-governmental organizations (NGOs) are involved in educating the public about the importance of patriotism.